Do Renovation of Kominka Offer an Efficient Path to Town Revitalization and Energy Efficiency? - Shrestha, Aakriti; Shimizu, Takafumi (MAJ - Malaysia Architectural Journal, 2025)
In Japan, collaborative public-private efforts are being made to renovate and reutilize the older buildings with the aim of preserving historic townscape and adapting them for commercial and communal needs. Subsidies are granted for maintenance and renovations of these buildings, which have attracted local businesses (cafes, shops, and offices) and have become venues for cultural activities, and gatherings. Renovations are done with no external wall insulation as it alters building physical characteristics and conservation principles, whereas internal walls are avoided as they are designed to facilitate the community. However, the energy cost of such buildings is generally high that can discourage people using them in the long-term thus, affecting town revitalization approaches. Therefore, it is important to understand the actual thermal environment of renovated old houses for sustainable and economically viable town development. With this aim, we surveyed a newly renovated kominka, now used as multipurpose library to understand the temperature distribution in shared and private spaces with and without use of air conditioning systems during the winter month. Similarly, the thermal characteristics of building elements were studied using a thermal camera, which shows uneven thermal distribution and leakages through the wall, floor, and roof after using AC. The surveyed building was renovated with the approximate cost of 150 million yen, with this study we can assume, there will be additional burden of annual energy cost due to the poor thermal insulation. Thus, there is a need for energy efficient renovation approaches.